Profiles of apple allergen components and its diagnostic value in Northern China - Wang, Xiaoyan; Chen, Lijia; Lan, Tianfei; Wang, Hongtian; Wang, Xueyan (Frontiers in Medicine, 2024)
Background Limited is known on the profiles of apple allergy in China. Objective To explore the clinical significance of apple allergen components in northern China. Methods This study recruited 40 participants and categorized into apple tolerance (n = 19) and allergy (n = 21) group. The latter was categorized into oral allergy symptoms (OAS, n = 14) and generalized symptoms (GS, n = 7). All participants underwent ImmunoCAP screening to assess sIgE levels of birch, apple, and their components. Results The sensitization rates were 90% for Bet v 1, 85% for Mal d 1, 35% for Bet v 2, and 20% for Mal d 3. The overall positive rate for apple allergens was 97.5%, with half demonstrating mono-sensitization to Mal d 1. Birch, Bet v 1 and Mal d 1 sIgE levels had consistent areas under the curve (AUC 0.747, p = 0.037; AUC 0.799, p = 0.012; AUC 0.902, p < 0.001 respectively) in diagnosing apple allergy. The optimal cut-off values were determined to be 22.85 kUA/L (63.6% sensitivity, 85.7% specificity), 6.84 kUA/L (81.8% sensitivity, 71.4% specificity) and 1.61 kUA/L (93.8% sensitivity, 75.0% specificity), respectively. No allergens or components demonstrated diagnostic value in distinguishing between OAS and GS. Mal d 3 sensitization was correlated with mugwort allergy and higher risk of peach, nuts or legumes generalized allergy. Conclusion Mal d 1 was major allergen and the best for diagnosing apple allergy. Mal d 3 does not necessarily indicate severe allergic reaction to apples in northern China but may indicate mugwort sensitization and an increased risk of peach, nuts or legumes allergy.